MEMIMPIN GENERASI MIGRAN:: PERAN GEREJA DALAM MENDORONG DAN MEMBANTU REMAJA DALAM PERJALANAN MENUJU IMAN - sopia; Bantara , Beny Christison (Jurnal Teologi RAI, 2024)
Taking care of generations of migrants is challenging considering the current conditions of globalization and migration. When it comes to encouraging and supporting young people on busy lives and spiritual journeys, the Church plays an important role. provides a summary of the role of the church in helping the young generation of migrants meet their needs and enhance their religious identity. Young migrants can receive spiritual formation and welfare in the church through pastoral, social, and educational approaches. In this view, the church plays an important role in helping the young generation of migrants grow and develop into citizens who are responsible, moral, and have a strong sense of self-confidence. The Church supports young people in overcoming obstacles and realizing their full potential so that they can make meaningful contributions to their communities and countries through education and spiritual growth. The Church also plays a role in providing a supportive community, supportive environment, and relevant religious instruction through various projects and programs. It consists of social initiatives, religious groups, and weekly religious services aimed at meeting the spiritual and social needs of young migrants. This study looks at the potential and problems that arise in helping young people from migrant backgrounds develop a solid and lasting faith and the role that churches may play in supporting and encouraging this process. The findings of this research indicate that churches have a great opportunity to support migrant youth in their efforts to develop a strong and lasting faith. This article also discusses tactics and ideas that churches can use to effectively guide and engage with generations of migrants, enabling them to become catalysts for constructive change in their congregations and communities. Therefore, Church leaders are asked to take the initiative to actively engage and motivate young migrants to develop their spiritual and religious lives.